Design And Development Of Mucoadhesive Microspheres Of Chlorpheniramine Maleate For Nasal Delivery - Pathak, Riya; Pandey, Jaideo (Journal of Neonatal Surgery, 2025)
Drug delivery methods that allow for prolonged, close contact between the drug and the mucosa are known as mucoadhesive drug delivery systems. In order to prevent hepatic first-pass metabolism, increase residence time, and improve therapeutic efficacy, the current study aimed to produce mucoadhesive microspheres for nasal delivery. In our work, we used the Emulsification cross linking approach to create Chlorpheniramine maleate mucoadhesive microspheres with conjugation of chitosan. The microspheres were assessed in terms of their stability, in vitro drug release, in vitro mucoadhesion, percentage yield, particle size, entrapment efficiency, and swelling properties. Using SEM and FTIR technologies, microspheres were characterised. Each batch's average microsphere’s particle size was found compiling with in the desired/recommended range, ensuring that every batch had appropriate handling qualities. It was discovered that the range of drug encapsulation efficiency, percentage yield & percentage for mucoadhesion for all formulations were observed to justify the recommended range. When all of the formulations were tested for In-vitro drug release using phosphate buffer 6.8 pH, microspheres showed regulated drug release for up to six hours. According to the results gathered, mucoadhesive microsphere technology represents a very promising nasal delivery for improving patient compliance and delivering medication over an extended period of time